Multigroup higher order mediator on entrepreneurial intention using structural equation modeling - Zulkurnain Nazleen Nur Ain, Ahmad Sabri (Universiti Pendidikan Sultan Idris, 2016)
Multigroup higher order mediator on entrepreneurial intention using structural equation modeling by Zulkurnain Nazleen Nur Ain, Ahmad Sabri,